Long term outcomes in monoclonal gammopathy of renal significance. (29th May 2019) - Khera, Akhil; Panitsas, Fotios; Djebbari, Faouzi; Kimberger, Katja; Stern, Simon; Quinn, John; Rabin, Neil; Kothari, Jaimal; Alchi, Bassam; Haynes, Richard; Winearls, Christopher; Roberts, Ian; et al.
Summary: Unlike AL amyloid and cast nephropathy, the long‐term outcomes of monoclonal gammopathy of renal significance (MGRS) patients with other renal histopathologies remain unclear. It is uncertain if early intervention improves renal outcomes, because of a lack of evidence from prospective studies. In this retrospective study, we examined outcomes of 41 MGRS patients treated between 2004 and 2017 across five centres: four in the UK and one in the Republic of Ireland. The primary outcome measure was renal survival estimated by Kaplan–Meier product‐limit method. Thirty‐three patients (80·5%) were kappa light chain (LC) restricted. Twenty‐seven patients (65·9%) presented with LC deposition disease on renal histology. At 24 months follow‐up, estimated renal survival was 81·6% for the whole cohort. The estimated overall survival was 80·3% at 48 months. At 24 months, patients who had chronic kidney disease (CKD) stage 2–3b at diagnosis showed an estimated renal survival of 100% compared to 80·7% in those with CKD stage 4–5 at diagnosis ( P  = 0·04). Poorer outcomes in MGRS patients were historically attributed to delayed diagnosis due to small plasma cell clones, as well as the need for renal biopsy.